2021
DOI: 10.1016/j.tube.2020.102033
|View full text |Cite
|
Sign up to set email alerts
|

Host transcriptional response to TB preventive therapy differentiates two sub-groups of IGRA-positive individuals

Abstract: We hypothesised that individuals with immunological sensitisation to Mycobacterium tuberculosis ( Mtb ), conventionally regarded as evidence of latent tuberculosis infection (LTBI), would demonstrate binary responses to preventive therapy (PT), reflecting the differential immunological consequences of the sterilisation of viable infection in those with active Mtb infection versus no Mtb killing in those who did not harb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…For TB diagnostics, improved approaches for both TB infection and TB disease are required. For TB infection, more advanced assays for pathogen detection, in addition to immunological sensitisation are needed [ 94 , 95 ], as are tools to determine viable bacilli that are likely to cause future disease [ 96 , 97 ]. For TB disease, microbiological evaluations using traditional respiratory specimens require optimisation, and newer diagnostics, using biomarkers in blood and urine, should be applied [ 98 , 99 ].…”
Section: Knowledge Gaps and How To Address Themmentioning
confidence: 99%
“…For TB diagnostics, improved approaches for both TB infection and TB disease are required. For TB infection, more advanced assays for pathogen detection, in addition to immunological sensitisation are needed [ 94 , 95 ], as are tools to determine viable bacilli that are likely to cause future disease [ 96 , 97 ]. For TB disease, microbiological evaluations using traditional respiratory specimens require optimisation, and newer diagnostics, using biomarkers in blood and urine, should be applied [ 98 , 99 ].…”
Section: Knowledge Gaps and How To Address Themmentioning
confidence: 99%
“…Pulmonary tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis attacking lungs [ 29 ]. In three transcriptome datasets (GSE28623 [ 30 ], GSE153340 [ 31 ], and GSE152532 [ 32 ]), TB patients showed greater VTP values than normal controls ( P < 0.001) ( Figure 2(d) ). Moreover, in GSE152532 and GSE28623 [ 30 ], VTP values likely followed the pattern: active TB > latent TB > normal controls ( Figure 2(d) ).…”
Section: Resultsmentioning
confidence: 99%
“… 32 We have also previously found that metformin has minimal impact on circulating blood transcriptomes, 61 as do TB drugs. 62 Our study was also too small to perform a stratified analysis based on the type of poor outcome, i.e. death, default, treatment failure or recurrence after treatment completion.…”
Section: Discussionmentioning
confidence: 96%